2020
DOI: 10.3390/antiox9010038
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia Improves Hind Limb Motor Outcome and Attenuates Oxidative Stress and Neuronal Damage in the Lumbar Spinal Cord Following Cardiac Arrest

Abstract: Hypothermia enhances outcomes of patients after resuscitation after cardiac arrest (CA). However, the underlying mechanism is not fully understood. In this study, we investigated effects of hypothermic therapy on neuronal damage/death, microglial activation, and changes of endogenous antioxidants in the anterior horn in the lumbar spinal cord in a rat model of asphyxial CA (ACA). A total of 77 adult male Sprague–Dawley rats were randomized into five groups: normal, sham ACA plus (+) normothermia, ACA + normoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
5
14
0
Order By: Relevance
“…Usually, ACA was confirmed at 3-4 min after vecuronium bromide injection in this study. Perfect ACA was confirmed when pulseless electric activity (PEA) was shown and mean arterial pressure (MAP) was below 25 mmHg [8,9]. ACA was maintained for 5 min.…”
Section: Aca/cpr Operation and Ris Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually, ACA was confirmed at 3-4 min after vecuronium bromide injection in this study. Perfect ACA was confirmed when pulseless electric activity (PEA) was shown and mean arterial pressure (MAP) was below 25 mmHg [8,9]. ACA was maintained for 5 min.…”
Section: Aca/cpr Operation and Ris Treatmentmentioning
confidence: 99%
“…Subsequently, manual chest compressions were performed. Namely, manual chest compression was performed at a rate of 300/min until MAP increased to 60 mmHg, and electrocardiography was checked [8,9]. Once each rat breathed and was hemodynamically stable, which was usually shown 1 h after ROSC, the catheter was removed.…”
Section: Aca/cpr Operation and Ris Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, it has been reported that hypothermic therapy can effectively reduce the histopathological damage of lumbar spinal cord (18,19), hippocampus (20) and cerebellum (21) in the brain of a rat model of asphyxial CA. However, as aforementioned, few studies have examined the effects of hypothermia on the liver after CA.…”
Section: Effects Of Hypothermia On Inflammatory Cytokine Expression In Rat Liver Following Asphyxial Cardiac Arrestmentioning
confidence: 99%